Antibodies to filamentous actin (F-actin) in type 1 autoimmune hepatitis. Issue 3 (27th February 2006) - Granito, A; Muratori, L; Muratori, P; Pappas, G; Guidi, M; Cassani, F; Volta, U; Ferri, A; Lenzi, M; Bianchi, F B
Abstract : Aims: To evaluate the diagnostic significance of anti-filamentous actin antibodies (A-FAA) assessed with a commercial ELISA in comparison with immunofluorescence reactivity and patterns of anti-smooth muscle antibodies (SMA); and to correlate A-FAA positivity with clinical, immunogenetic, laboratory, and histological features in patients with autoimmune hepatitis type 1 (AIH-1). Methods: We studied 78 consecutive untreated AIH-1 patients and 160 controls: 22 with autoimmune hepatitis type 2 (AIH-2), 51 with hepatitis C, 17 with coeliac disease (CD), 20 with primary biliary cirrhosis (PBC) and 50 blood donors. SMA was evaluated by indirect immunofluorescence (IIF) on frozen sections of rat tissues, and A-FAA with a modified commercial ELISA. Results: SMA was detected by IIF in 61 (78%) of 78 AIH-1 patients, of whom 47 (60%) had the SMA-T/G and 14 (18%) the SMA-V pattern. Of the pathological controls, 32 (20%) had the SMA-V pattern (25 with hepatitis C, 2 with AIH-2, 2 with PBC, 3 with CD). A-FAA were present in 55 AIH-1 patients (70.5%; 46 with SMA-T/G, 7 with SMA-V, and 2 SMA-negative), and in 10 controls (6%), of whom five had hepatitis C, two AIH-2, two PBC and one CD. The association between A-FAA and the SMA-T/G pattern was statistically significant (p<0.0001). A-FAA levels were higher in SMA-T/G positive than SMA-V positive AIH-1 patients and controls (p<0.0001). A-FAA positivity was significantly associated with higher γ-globulin and IgG levels, but did not correlate with other considered parameters. Conclusion: The modified A-FAA ELISA strictly correlates with the SMA-T/G pattern and is a reliable and operator independent assay for AIH-1. Detection of A-FAA, even if devoid of prognostic relevance, may be useful when interpretative doubts of standard IIF arise.